2008
DOI: 10.1074/jbc.m802053200
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase Phosphorylates and Desensitizes Smooth Muscle Myosin Light Chain Kinase

Abstract: Smooth muscle contraction is initiated by a rise in intracellu-The activity of smMLCK itself can be modulated by phosphorylation, which changes its V max or affinity for Ca 2ϩ /CaM. smMLCK is phosphorylated at two sites (7, 8) by cAMP-dependent protein kinase (PKA). One site (site A, corresponding to Ser 815 in chicken and Ser 992 in rabbit smMLCK and conserved in the human, mouse, and rat sequences) lies in the C-terminal CaM-binding domain. Treatment with PKA inactivates MLCK by decreasing its affinity for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 41 publications
7
131
1
Order By: Relevance
“…STO-609, an inhibitor of CaMKK␤, has been used to demonstrate the role of CaMKK␤ in AMPK activation (40,55,56). Here, we found that STO-609 had no effect on the increase in O-GlcNAc, even at concentrations as high as 80 M, suggesting that CaMKK␤-mediated AMPK activation was not a contributing factor in the response to glucose deprivation.…”
Section: Discussionmentioning
confidence: 55%
“…STO-609, an inhibitor of CaMKK␤, has been used to demonstrate the role of CaMKK␤ in AMPK activation (40,55,56). Here, we found that STO-609 had no effect on the increase in O-GlcNAc, even at concentrations as high as 80 M, suggesting that CaMKK␤-mediated AMPK activation was not a contributing factor in the response to glucose deprivation.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast to this observed AMPK-MRLC pathway, deletion of Lkb1 in the pancreatic epithelium does not lead to a decrease in p-MRLC (Ser19) . Moreover, the MRLC pathway is inhibited rather than activated by AMPK in vascular smooth muscle cells (Horman et al, 2008).…”
Section: Mechanisms Of Polarity Controlmentioning
confidence: 99%
“…The AMPK-null mutation in Drosophila is lethal, producing severe defects in cell polarity and mitosis; it was shown that nonmuscle myosin regulatory light chain was phosphorylated directly by AMPK, and the expression of a phosphomimetic light chain was found to rescue the cell polarity and mitosis phenotype. 49 AMPK phoshorylates and desensitizes smooth muscle myosin light chain kinase 50 and has been shown to be involved in the regulation of Drosophila visceral smooth muscle via myosin light chain phosphorylation. 51 In mammalian cells, both the activated ␣ subunit and the ␥2 subunit have been localized to distinct position in the cytokinetic apparatus, 52,53 and in epithelial cells the kinase has also been shown to mediate reorganization of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…All data acquisition and analysis were performed in a blinded fashion. pCa 50 in the recording chamber. LV myocyte length was measured by using a video-edge detection system (IonOptix Corp, field stimulation at 3Hz).…”
Section: Force Measurements In Skinned Preparationsmentioning
confidence: 99%